The advantages of a single use retractor for soft tissue protection in direct anterior approach total hip arthroplasty: the preliminary experience - Giaretta, Stefano; Spolettini, Pietro; Raimondi, Marco; Momoli, Alberto (Acta Biomedica Atenei Parmensis, 2023)
The anterior hip approach is a procedure with increasing popularity in hip replacement surgery due to its many benefits and the number of surgeons using it is steadily increasing around the world. Less pain, better results in the first few weeks, reduced dislocation rate are the prerogatives of this approach.We analyzed in a group of 26 patients the use of a soft tissue retractor, Alexis Orthopedic Protector, the CPK values in the first third and fifth postoperative day. The results obtained, normalized, demonstrate a slight reduction in tissue damage using the device compared to a control group. In addition to blood values, improved exposure, distribution of leverage, cleanliness of the field and a potential reduction in infectious risk are advantages for the use of an orthopedic surgery retractor.We believe that the adoption of the Alexis Orthopedic Protector provides numerous improvements during the hip arthroplasty surgical procedure, especially when adopting the direct anterior approach, because it distributes the traction forces around the surgical path resulting in greater visibility. However, the small number of patients is not sufficient to perform an accurate statistical analysis and further studies on larger samples will be required.